Tamiko and the two janitors eaudiobook Amaranthine saga series, book 3. - Forthright (Amaranthine Saga, 2019)
In doing her part for world peace, she puts one crosser's whole world at risk. Conspiracy theories, werewolf scares, and protest rallies have hampered the peace process in America, where social and political unrest keep most Amaranthine from declaring themselves. Those not in seclusion rely heavily on illusion to mask their true nature. As the newly appointed principal of a small elementary school, Tamiko Reaverson is doing her part for world peace. She rallies her community's support and applies for Hisoka Twineshaft's school revitalization project, which will bring Amaranthine to her hometown. Little does Tami realize that Fletching was founded by one of the oldest and largest urban enclaves in the United States. And two of her staunchest supporters—janitors at her school—share a secret neither wants exposed.